2014
DOI: 10.1515/ehs-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vibration Energy Harvesting Through Multilayer Textured Pb(Mg1/3Nb2/3)O3–PbZrO3–PbTiO3 Piezoelectric Ceramics

Abstract: High-performance low-cost multilayer textured Pb(Mg 1/3 Nb 2/3 )O 3 -PbZrO 3 -PbTiO 3 (PMN-PZT) piezoelectric ceramic benders were fabricated by combining templated grain growth (TGG) and low-temperature co-firing ceramics (LTCC) process. The d  g values of textured samples were 700-800% higher than that of the random counterpart, which results in 500-600% increase in the output power from vibration energy harvesting. The output power and power density of tri-layer textured sample at the acceleration of 0.43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…High output power and power density of tri-layer textured ceramics were found to be 903 μW and 15.5 mW/cm 3 . This textured ceramics is a promising material for power sources and meets the requirement of sensor nodes in requisite package [84]. Table 4 summarizes the properties of typical PZT-based ceramics applied for PEH.…”
Section: Texturing To Pzt-based Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…High output power and power density of tri-layer textured ceramics were found to be 903 μW and 15.5 mW/cm 3 . This textured ceramics is a promising material for power sources and meets the requirement of sensor nodes in requisite package [84]. Table 4 summarizes the properties of typical PZT-based ceramics applied for PEH.…”
Section: Texturing To Pzt-based Ceramicsmentioning
confidence: 99%
“…In 2015, Kch et al [84] Hou et al [97] found that the simple composition of (Na 0.5 K 0.5 ) 0. 94 Table 5 summarizes the properties of typical lead-freebased piezoelectric materials for PEH, which mainly focus on the KNN-based ceramics and BNT-based ceramics.…”
Section: Lead-free Piezoelectric Ceramicsmentioning
confidence: 99%
“…10 However, the ST template was unstable in the specimen, resulting in a decrease in T C . 12,13 In addition, the TGG process was also used for the synthesis of high performance lead-free piezoelectric ceramics such as (Bi 1-x Na x )TiO 3 and (K 1-x Na x )NbO 3 ceramics. 11 The [001]-textured PMN-Pb(Zr,Ti)O 3 ceramics were also investigated for application to piezoelectric energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…The use of piezoelectric materials, such as macro-fiber composite (MFC) and lead zirconate titanate (PZT), to harvest storable energy from ambient vibrations is a well-developed research area (Williams et al 2002;Priya and Inman 2009). Although it provides a good alternative to using batteries and in spite of continuous advancements to enhance the performance of electromechanical parameters through grain texturing (Yan et al 2014), piezoelectric based energy harvesting remains limited by the low levels of available energy, low level of harvested energy due to the low efficiency of transduction mechanisms and more importantly by the input fluctuations which results in highly intermittent harvested power. To overcome these limitations, the energy harvester can be complemented with an energy storage device that can be used to ensure continuous operation of self-powered systems.…”
Section: Introductionmentioning
confidence: 99%